Intranasal Ketamine for Depression in Adults: A Systematic Review and Meta-Analysis of Randomized, Double-Blind, Placebo-Controlled Trials - An, Dongjiao; Wei, Changwei; Wang, Jing; Wu, Anshi (Frontiers in Psychology, 2021)
Background There is growing interest in glutamatergic agents as a treatment for depression, especially intranasal ketamine, which has become a hot topic in recent years. We aim to assess the efficacy and safety of intranasal ketamine in the treatment of major depressive disorder (MDD), especially treatment-resistant depression (TRD). Methods We searched Medline, EMBASE, and the Cochrane Library until April 1, 2020 to identify double-blind, randomized controlled trials with allocation concealment evaluating intranasal ketamine in major depressive episodes. Clinical remission, response, and depressive symptoms were extracted by two independent raters. The outcome measures were Montgomery–Asberg Depression Rating Scale (MADRS) score improved from baseline, clinical response and remission, dissociative symptoms, and common adverse events. The analyses employed a random-effects model. Results Data were synthesized from five randomized controlled trials (RCTs) employing an intranasal esketamine and one RCT employing intranasal ketamine, representing 840 subjects in parallel arms, and 18 subjects in cross-over designs (n = 858 with MDD, n = 792 with TRD). The weighted mean difference of MADRS score was observed to decrease by 6.16 (95% CI 4.44–7.88) in 2–4 h, 9.96 (95% CI 8.97–10.95) in 24 h, and 4.09 (95% CI 2.18–6.00) in 28 day. The pooled relative risk (RR) was 3.55 (95% CI 1.5–8.38, z = 2.89, and p < 0.001) for clinical remission and 3.22 (95% CI 1.85–5.61, z = 4.14, and p < 0.001) for clinical response at 24 h, while the pooled RR was 1.7 (95% CI 1.28–2.24, z = 3.72, and p < 0.001) for clinical remission and 1.48 (95% CI 1.17–1.86, z = 3.28, and p < 0.001) for clinical response at 28 day. Intranasal ketamine was associated with the occurrence of transient dissociative symptoms and common adverse events, but no persistent psychoses or affective switches. Conclusion Our meta-analysis suggests that repeated intranasal ketamine conducted a fast-onset antidepression effect in unipolar depression, while the mild and transient adverse effects were acceptable. Systematic Review Registration PROSPERO, CRD42020196856.